1997
DOI: 10.1056/nejm199707103370201
|View full text |Cite
|
Sign up to set email alerts
|

Trial of Calcium to Prevent Preeclampsia

Abstract: Calcium supplementation during pregnancy did not prevent preeclampsia, pregnancy-associated hypertension, or adverse perinatal outcomes in healthy nulliparous women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
188
2
10

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 551 publications
(202 citation statements)
references
References 21 publications
2
188
2
10
Order By: Relevance
“…In this regard, Purwar et al have reported that preeclampsia in a calcium group was 2% and in placebo group was 12% and this difference was significant 15 . But Levine et al have found no difference between calcium and placebo group in preeclampsia 16 . Belizán et al have demonstrated that the incidence of preeclampsia in the placebo group was 4% and in calcium group was 3%, which did not differ significantly 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Purwar et al have reported that preeclampsia in a calcium group was 2% and in placebo group was 12% and this difference was significant 15 . But Levine et al have found no difference between calcium and placebo group in preeclampsia 16 . Belizán et al have demonstrated that the incidence of preeclampsia in the placebo group was 4% and in calcium group was 3%, which did not differ significantly 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Women took 86% of the supplement on average, increased their urinary excretion of calcium, and had a reduced risk of pregnancy-induced hypertension and preeclampsia although, in the case of the latter, the 95% CI of the odds ratios included unity. In contrast, the trial conducted by the NIH studied the effect of calcium supplementation (2000 mg/d) Same nutrient, different hypotheses: disparities in trials of calcium supplementation during pregnancy [1][2][3] in 4336 women without a calcium deficiency (mean baseline intake: 1130 mg/d) to achieve a pharmacologic, preventive effect rather than to correct a nutritional deficit (1). Women took an average of 64% of the supplement and only 20% of them used > 90% of the medication (1).…”
Section: Disparities Between the 2 Largest Trialsmentioning
confidence: 99%
“…These RRs are not statistically significant, probably because of a smaller number of events in the subgroup analysis. Because actual numbers were not provided, it was not possible to evaluate further these stratified data (1). A reassuring finding is that, even in a population with such a high total calcium intake (Ϸ3 g/d), there was no significant difference between groups in the rate of urolithiasis during pregnancy or neonatal hypocalcemia (1).…”
Section: Disparities Between the 2 Largest Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent examples (5)(6)(7)(8) have been encountered where large randomized trials reached entirely different conclusions when compared with metaanalyses of earlier trials of small or even large sample size on the same question. For example, recent large trials seemed to invalidate our prior beliefs about the efficacy of treatments such as magnesium salts and nitrates for reducing overall mortality in acute myocardial infarction (9) or aspirin (10) and calcium supplementation (11) for the prevention of preeclampsia during pregnancy. Prior expectations of 30-60% reductions in mortality and preeclampsia, respectively, based on early trials, were not confirmed.…”
mentioning
confidence: 99%